Social constraints of aspirations for second language achievement - Rokita-Jaśkow, Joanna (Theory and Practice of Second Language Acquisition, 2018)
Educational aspirations are dfined a ;educational goals students set for themselves' ( Trebbels, 2015:37). They are widely studied in psychological and sociological research, in which it was found that 1) they form in late adolescence and early childood, 2) their goal and level (i.e. high vs. low) are determined by the social environmnet they come from, i.e. their family background, peer and school influence. The paper presents the results of the qualitative study, in which 56 students of English philology in one of the vocational schools in the south of Poland expressed their aspirations in reference to their future foreign language attainment and associated vocational goals. The results showed that in the majority of cases the aspirations are not so high and fully-formed, which, it is hypothesised is rooted in the social background the students come from.